Upper German Dialects as a Linguo-Cultural Phenomenon - G. А. Baeva; A. A. Ponomareva (Дискурс)
Introduction. The study attempts to reveal the role of the dialect as a linguo-cultural phenomenon through the prism of its semantics. The lack of studies on dialects from the linguo-cultural point of view – modern cultural linguistics is mostly focused on standard languages and national cultural codes – determines the novelty and relevance of this issue. Methodology and sources. The research content consists of more than 100 Bavarian and Swabian dialect words which reflect culture specifics of each region, selected from the 20th- 21st centuries fiction, regional media materials and local advertising by using the systematic sampling method. To identify the regional culture specifics, the study provides a two-level method, based on the analysis of lexicographic sources and results of the interview and questionnaire of 66 respondents. The updated range of denotative and connotative meanings of each lexeme is considered within 10 thematic groups.Results and discussion. It has been found out that the researched dialects clearly reflect the South German regional tradition and history which can be traced in the semantics of the dialect words. Despite the globalization, a partly similar historical development of the two regions, as well as the belonging of the Bavarian and Swabian dialects to the same dialect continuum, the analysis of the dialect semantic structures within thematic groups revealed some similarities and differences which lead to conclusions regarding the specifics of the South German linguo-cultural code.Conclusion. It has been concluded that the further study on linguistic variety from the interdisciplinary point of view, including cultural linguistics and pragmatics, allows to better understand the role of dialect in modern communication.